Developing undergraduate students employability through career development learning - Wujema, Baba Kachalla; Mohd Rasdi, Roziah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Increasing unemployment due to lack of proper career guidance, career choices and decreasing employability skills among undergraduate students has hampered the effectiveness of career development learning among university students in Nigeria. This inadequate career guidance programmes in the universities has led to many students graduating with careers different from the needs of the employers. This study is based on an extensive review of past research on employability and career development learning. Literature review was conducted alongside DOTS Model. John Holland’s theory on career choice and development further added more support to the paper. In order to develop undergraduate students employability upon graduation, Nigerian universities should therefore strengthen their efforts in developing appropriate strategies so as to engage undergraduate students with the domains of career development as portrayed in the DOTS model. More so, the study will call for adequate provision of career development programmes in the universities, as that will provide an avenue for potential graduates to possessed skills, work experience, interview techniques, job search skills and networking which will consequently provide employment generation in the country.